Contributive Roles of Sorghum Production to Food Security and Economic Empowerment of Rural Farming Households in Katsina State, Nigeria - O., Oyediran, W.; M., Omoare, A.; A., Osinowo, O. (Canadian Journal of Agriculture and Crops, 2017)
Sorghum is an important food and economic crop in Nigeria. However, the full potential of the crop for domestic and industrial uses has not been harnessed in Nigeria. This study was conducted to assess the roles of sorghum in food security and economic empowerment of rural farming households with the view to promote its productivity in Katsina State. Simple random sampling technique was used to select 215 sorghum farmers for this study. Descriptive statistics and chi-square analysis were used to analyze the data. Result of the study revealed that sorghum production immensely contributed to food (89.3%), job (86.5%) and income (70.7%) of the rural farming households in the study area. Also, result of chi-square analysis showed that there is significant association between constraints and roles of sorghum in household food security and economic empowerment at p < 0.05 level of significance. The study concluded that sorghum production contributed to household food security and economic empowerment in the study area.